Pericardial Metastasis Induced Tamponade from Urothelial Carcinoma: A Rare Entity - Khan, Rafay (Case Rep Med, 2016)
Urothelial carcinoma in a few cases may result in cardiac metastasis. A rare presentation of this condition is its diagnosis as a result of cardiac tamponade. Tamponade is an unusual entity as a result of urothelial carcinoma and has only been reported in four cases. There have also been only a total of fifteen cases of cardiac metastasis from this form of malignancy. It is through this discussion that we emphasize the importance of early detection and monitoring of cardiac symptoms with the implementation of echocardiogram imaging. Although not feasible in all patients it may be considered in those presenting with cardiac and pulmonary symptoms. In this case we discuss the presentation of a 71-year-old gentleman with a history of urothelial carcinoma after cystectomy and while on chemotherapy presented with new onset atrial fibrillation and later was diagnosed with cardiac tamponade as a result of malignant metastasis.